Integrative analyses of metabolome and transcriptome identifies the potential mechanism of Aureobasidium pullulans PA-2 inhibiting Chenopodium album L. growth - Shan-shan Mo; Han-feng Gao; Ying Yang; Juan Li; Xin Wang; Hai-xia Zhu; You-hai Wei; Qing-yun Guo; Liang cheng (BMC Plant Biology)
Abstract Background Chenopodium album L. is one of the most important threat weeds affecting crops productivity in the fields. Control of this weed is complex and currently, lies in the use of chemical methods, although this method has not proven to be fully effective. The utilization of microorganisms has emerged as a means of simultaneously controlling this weed with high-efficiency, and friendly to the environment. In this regard, this study used LC-MS/MS and RNA-Seq technology to gain insights into the molecular herbicidal mechanisms underlying strain Aureobasidium pullulans PA-2 on C. album. Results Physiological and biochemical tests showed that compared with the control group (CK), the content of chlorophyll, soluble protein, soluble sugar and phenylalanine ammonia-lyase (PAL) activity in C. album leaves in the pot show a decreasing trend under the infection of PA-2. Transmission electron microscopy (TEM) observation revealed that abnormal shapes of chloroplast, incomplete intracellular structure and gradual disintegration of the outer membrane in the cells of C. album are observed at the third day after inoculation. A total of 69,404 unigene was obtained, among which 35,950 were differentially expressed genes (DEGs), and most of them were enriched plant secondary metabolite biosynthesis, phytohormone signaling, and carotenoid biosynthesis. Moreover, the analysis of 8 candidate genes showed that the content of photosynthesis indices was significantly decreased, which was resulted from the down-regulation of photosynthesis-related genes expression levels after PA-2 infection. During the PA-2 infection phase, a total of 14,521 and 13,211 differentially accumulated metabolites (DAMs) were identified using the ESI+ and ESI− modes, respectively. Significant differences were observed in the content of DAMs at the five stages of PA-2 infection, especially photosynthesis, purine metabolism, and carotenoid biosynthesis. Further correlation analysis of major DAMs and DEGs showed that 19 key DEGs were involved in photosynthesis, 10 key DEGs in carotenoid biosynthesis, and 3 key DEGs in purine metabolism. Conclusion These findings have paved way in further functional characterization of candidate genes and subsequently can be better understanding of molecular mechanism of PA-2 infection on C. album.